2014
DOI: 10.1111/tmi.12263
|View full text |Cite
|
Sign up to set email alerts
|

Associations between presence of handwashing stations and soap in the home and diarrhoea and respiratory illness, in children less than five years old in rural western Kenya

Abstract: OBJECTIVE We tested whether soap presence in the home or a designated handwashing station was associated with diarrhoea and respiratory illness in Kenya. METHODS In April 2009, we observed presence of a handwashing station and soap in households participating in a longitudinal health surveillance system in rural Kenya. Diarrhoea and acute respiratory illness (ARI) in children < 5 years old were identified using parent-reported syndromic surveillance collected January–April 2009. We used multivariate generali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 33 publications
5
30
1
1
Order By: Relevance
“…Although results are mixed when looking at the association between a designated place for handwashing and respiratory and diarrhea symptoms in children below the age of 5, 22,29 some studies have found increased handwashing behavior in households with a fixed handwashing location. 19,30 Interactions between fixed and self-created contextual factors.…”
Section: Introductionmentioning
confidence: 99%
“…Although results are mixed when looking at the association between a designated place for handwashing and respiratory and diarrhea symptoms in children below the age of 5, 22,29 some studies have found increased handwashing behavior in households with a fixed handwashing location. 19,30 Interactions between fixed and self-created contextual factors.…”
Section: Introductionmentioning
confidence: 99%
“…According to Kamm et al (2014), washing hands with soap can prevent child mortality caused by two major killer diseases of pneumonia and diarrhea. Handwashing behavior using soap with water can remove dirt and pathogen in the hand, physically it can reduce the transmission of pathogen.…”
Section: The Association Between Healthymentioning
confidence: 99%
“…Esse achado pode estar diretamente relacionado à incidência de diarreia encontrada nesta pesquisa, porque a taxa de parasitoses intestinais é menor entre as pessoas que realizam filtração da água antes de consumir (20) . Verificou-se que 96,6% da amostra referiram realizar a lavagem das mãos com água e sabão, ação importante na prevenção de diarreia, já que estudo realizado na zona rural do Quênia concluiu que o índice de prevalência de diarreia em crianças menores 5 anos reduziu 41% em residências que possuíam sabão para fazer a higienização das mãos quando comparadas com residência que não o possuíam (21) .…”
Section: Discussionunclassified